Development of an Online-Coaching Blended Couple-Oriented Intervention for Preventing Depression in Middle Adulthood: An Intervention Mapping Study - Kim, Suk-Sun; Gil, Minji; Kim, Daeun (Frontiers in Public Health, 2022)
Background Although middle-aged adults in Korea are vulnerable to depression, there are few preventive interventions for depression in middle adulthood. Studies consistently suggest that interventions that include both spouses are effective in decreasing depression and relationship distress. Considering the busy lives of middle-aged couples, it is essential to develop an online-coaching blended couple-oriented intervention. This study aimed to describe the development, implementation, and evaluation of an online-coaching blended couple-oriented intervention using an online program and coaching via videoconference to prevent middle-aged couples' depression; this was done using an intervention mapping (IM) protocol. Methods Six steps of IM were used to systematically develop a tailored multi-level intervention specific to middle-aged couples' depression. These steps of the IM protocol involve needs assessment, formulation of change objectives, theory-based methods, and practical strategies for program design, program development, program implementation, and program evaluation. Results The results of the six steps were as follows: (a) middle-aged couples' needs and mental health problems were identified through a scoping review study, mixed-method study, and expert interviews; (b) six performance objectives (POs) were formulated based on the results of Step 1, and intrapersonal, interpersonal, and temporal/transpersonal determinants were identified based on the self-transcendence theory. Change objectives were developed by combining POs with determinants; (c) self-regulated learning was chosen for theoretical teaching methods and practical strategies to change the determinants of each level; (d) four modules consisting of 16 sessions were developed based on the self-transcendence theory; (e) experts evaluated the program and coaches were trained; and (f) the evaluation plan for the program's feasibility, acceptability, usability, and preliminary effects was developed. Discussion The systematic process using IM allowed us to develop an online-coaching blended couple-oriented intervention to prevent depression and promote couples' relationships. The primary effects of this newly developed program should be evaluated in future studies. This may lead to the increased adoption and implementation of evidence-based and tailored interventions for psychological wellbeing in middle adulthood.